Sustainable Consumer Behavior of Halal Cosmetics in Indonesia E-Commerce: A Maslahah-Based Approach - Al Farisi, Muhammad Salman; Anwar, Syamsul; Haryono, Slamet; Wahid, Hariyaty Ab (IQTISHODUNA: Jurnal Ekonomi Islam, 2025)
This research aims to analyze whether the consumption of halal cosmetic products has different priority scales based on maslahah orientation and whether subjective attitudes and norms, and technology acceptance affect consumer intentions and behavior based on maslahah elements in the consumption of halal cosmetic products. The research method for this   uses a combination research that combines two approaches to research, namely quantitative and qualitative. The number of samples in the quantitative research were 250 respondents. The number of samples in qualitative research is ten respondents. Data was collected by interviewing the respondents. Quantitative data analysis techniques use structural equation models or Structural Equation Modeling (SEM) which are processed using SmartPLS 3.0 software. The results of this   research show that the conceptual model used in predicting consumer behavior for halal cosmetic products in Indonesia is a model that is built based on a model that integrates the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM) by adding the maslahah variable as another predictor in improving better predictive ability of consumer intentions and behavior. The consumer behavior of halal cosmetic products in e-commerce in Indonesia in the perspective of maslahah is included in the category of maslahah tahsiniyat or tertiary needs, which are needed by humans so that life becomes more comfortable and more beautiful. This research also addresses global concerns related to ethical consumption, digital trust, and faith-driven market behavior in emerging economies.